Edukasi Interaktif Jenis Jenis Sampah Untuk Anak Sejak Dini di Gampong Pancakubu Seulawah - Kamaly, Nurul; Fatih, Muhammad; Alfa, muhammad; Winda, Maulida; Alqarni, Wais (Yayasan Inspirasi El Burhani, 2025)
Introduction: Waste management remains a major environmental issue that requires early intervention through education. Children are a strategic age group to receive basic environmental education, especially in understanding the importance of sorting waste. However, the lack of age-appropriate and engaging learning media often hampers effective education. Objective: This community service program aimed to introduce different types of waste to early childhood students in Gampong Pancakubu Seulawah through an interactive and enjoyable educational approach, with the goal of fostering environmentally friendly behavior from an early age. Method: The activity employed a descriptive qualitative method using a participatory approach. Various media were utilized, including sorting games, illustrative images, educational videos, and direct practice in waste segregation. Observations were conducted to evaluate children’s responses and comprehension before and after the activity. Result: The interactive method significantly improved the children's understanding of organic, inorganic, and hazardous waste. The participants showed high enthusiasm, demonstrated the ability to classify different types of waste correctly, and began to adopt better habits in waste disposal. Conclusion: Interactive environmental education proved effective in raising environmental awareness among early childhood learners. This program not only increased knowledge but also instilled positive behavior that contributes to improved community-level waste management. This model is recommended for replication in other communities with appropriate local adjustments.